Venetoclax-based salvage therapy as a bridge to transplant is feasible and effective in patients with relapsed/refractory AML - Unglaub, Julia Marie; Schlenk, Richard Friedrich; Middeke, Jan Moritz; Krause, Stefan W.; Kraus, Sabrina; Einsele, Hermann; Kramer, Michael; Zukunft, Sven; Kauer, Joseph; Renders, Simon; Katelari, Elena; Schliemann, Christoph; et al. (Blood advances, 2025)
The B-cell lymphoma 2 inhibitor venetoclax (VEN) in combination with hypomethylating agents has been approved for first-line treatment of patients with acute myeloid leukemia (AML) ineligible for intensive treatment. VEN-containing treatment strategies may also be effective in relapsed/refractory (R/R) AML; however, comparative studies with conventional therapies for fit patients as a bridge-to-transplant strategy are limited. Using propensity score matching (PSM), we compared 37 patients with R/R AML, who received VEN-based salvage therapy as bridge to allogeneic hematopoietic stem cell transplantation (allo-HCT), with 90 patients from the German Study Alliance Leukemia AML registry, who were treated with non-VEN-containing salvage therapy according to their treating physician’s choice (TPC). The overall response rate among VEN patients was higher than the TPC control cohort (62% vs 42%; P = .049). Overall, 73% of VEN-treated patients vs 63% of TPC patients were bridged to allo-HCT (P = .41). After a median follow-up of 34.3 months for the VEN and 21.0 months for the TPC cohort, the median overall survival (OS) were 15.8 months (95% confidence interval [CI], 10.6 to not evaluable) and 10.5 months (95% CI, 6.8-19.6; P = .15), respectively. PSM revealed a trend toward improved OS for VEN patients (hazard ratio, 0.70; 95% CI, 0.41-1.22; P = .20). Median event-free survival was significantly longer in the VEN cohort (8.0 months) than the TPC cohort (3.7 months; P = .006). Our data suggest that VEN-based salvage therapy is a safe and effective bridge to allo-HCT for this difficult-to-treat AML patient population.
Gesehen am 26.09.2025